EP 45. Polymyositis? limb-girdle muscular dystrophy!. Issue 9 (September 2016) - Ceccon, G.; Lehmann, H.C.; Neuen-Jacob, E.; Fink, G.R.; Wunderlich, G.
Abstract : Limb-girdle muscular dystrophies (LGMD) are a group of progredient myopathic disorders, whose primary symptom is a progressive weakness of the proximal muscles. Most forms result from a gene dysfunction and are inherited in an autosomal recessive pattern. The phenotype an the age of onset vary between the different forms. A muscular biopsy can reveal signs of an inflammatory reaction in varying degree, though this is not necessary and occurs mostly in some subtypes. We report about a 32-year old female with severely elevated serum creatin kinase (80, 000 U/l), which had been found in a routine blood sample 7 years ago. She first presented at an internal medicine department. At that time, only a mild proximal muscle weakness was present at best and physical performance was not impaired at all. Electromyography already showed myopathic changes with abnormal spontaneous activity. Muscle biopsy revealed an inflammatory reaction with distinctive signs of necrosis. Further tests gave no evidence for a paraneoplastic or rheumatologic condition. Suspecting a polymyositis, an immunosuppressive treatment was initiated, first with glucocorticosteroids, later with Methotrexate, Azathioprine, cyclosporine, intravenous immune globuline, Mycophenolat mofetil and Rituximab. Nevertheless, there was no improvement neither of serum creatin kinase nor of the muscle weakness. Instead, the weakness gradually evolved into a tetraparesis. When she finally presented to our department, she could walk no more than a few steps and was not able to get up from a chair. The progressive course of the disease under sufficient immunosuppressive therapy let us think of a chronic degenerative process, such as a muscular dystrophy. Upon further inquiry, the from Sicily originating patient told us about a consanguinity of her parents. The late manifestation (no relevant symptoms until the age of 25, the highly elevated serum creatin kinase and the inflammation in the muscle biopsy were compatible to a dysferlinopathy, a subtype of limb-girdle muscular dystrophy. Genetic testing revealed a yet unknown homozygotic mutation in the dysferlin gene causing the disease. Unfortunately, no other treatment could be proposed to the patient besides physical and occupational therapy. In summary, even though elevated serum creatin kinase and inflammatory changes in the muscle biopsy often point to polymyositis, this is not always the case. In some types of autosomal recessive forms of LGMD (besides LGMD2B notably 2L, 2M and 2N) distinctive inflammatory changes can be detected histopathologically. Especially disease progression despite sufficient immunosuppressive therapy should lead to reevaluation of the diagnosis